In Situ Coupled Electrochemical-Goniometry as a Tool to Reveal Conformational Changes of Charged Peptides - Ghafari Amir Mohammad; Dominguez Sergio E.; Järvinen Ville; Gounani Zahra; Schmit Amandine; Sjöqvist Marika; Sahlgren Cecilia; Salo-Ahen Outi M. H.; Kvarnström Carita; Torsi Luisa; Österbacka Ronald (Wiley-VCH, 2025)
The opportunity to manipulate cell functions by regulating bioactive surfaces is a potentially promising approach for organic bioelectronics. Here, the tuning of the orientation of charged peptides by means of an electrical input observed via optical tensiometry is reported. A stimuli-responsive self-assembled monolayer (SAM) with specially designed charged peptides is used as a model system to switch between two separate hydrophilic states. The underwater contact angle (UCA) technique is used to measure changes in the wetting property of a dichloromethane droplet under electrical stimuli. The observed changes in the UCA of the bio-interface can be understood in terms of a change in the surface energy between the ON and OFF states. Molecular dynamics simulations in an electric field have been performed to verify the hypothesis of the orientational change of the charged peptides upon electrical stimulation. In addition, X-ray photoelectron spectroscopy (XPS) is performed to clarify the stability of the functionalized electrodes. Finally, the possibility of using such a novel switching system as a tool to characterize bioactive surfaces is discussed.